2021
DOI: 10.18585/inabj.v13i2.1501
|View full text |Cite
|
Sign up to set email alerts
|

Advance-Platelet Rich Fibrin and Hyaluronic Acid Combination Improves Interleukin-6 and Granulation Index in Diabetic Foot Ulcer Patients

Abstract: BACKGROUND: Diabetic foot ulcer (DFU) is the most common and threatening complication of Diabetes Mellitus (DM). Ideal wound dressing for DFU management should relieve symptoms, provide wound protection, and encourage healing. Advanced-Platelet Rich Fibrin (A-PRF) and Hyaluronic Acid (HA) have been proven to improve wound healing process. This study was aimed to demonstrate the ability of combination of A-PRF and HA in reducing inflammation and improving DFU tissue healing.METHODS: Twenty DFU subjects were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Which, apparently, is associated with the pleiotropy of IL-6 and with a wide spectrum of biological activity of the studied cytokine in immune regulation, hematopoiesis, and inflammation, as well as in metabolic, proliferative, and regenerative processes. (23,24) The results of our work show that in rats with arterial hypertension, IL-6 levels increased after fracture (group 2.2) compared to similar cytokine concentrations in SHR rats without surgery (group 2.1), and also significantly decreased in the serum of SHR animals with modeled fractures while taking enalapril (group 2.4) compared to levels IL-6 in SHR rats of group 2.3.…”
Section: Bioactive Molecules and Biochemical Parametersmentioning
confidence: 56%
“…Which, apparently, is associated with the pleiotropy of IL-6 and with a wide spectrum of biological activity of the studied cytokine in immune regulation, hematopoiesis, and inflammation, as well as in metabolic, proliferative, and regenerative processes. (23,24) The results of our work show that in rats with arterial hypertension, IL-6 levels increased after fracture (group 2.2) compared to similar cytokine concentrations in SHR rats without surgery (group 2.1), and also significantly decreased in the serum of SHR animals with modeled fractures while taking enalapril (group 2.4) compared to levels IL-6 in SHR rats of group 2.3.…”
Section: Bioactive Molecules and Biochemical Parametersmentioning
confidence: 56%
“…PRF is a safe, appropriate, easy-to-use adjunctive treatment modality with substantial possibility for the management of chronic skin wounds like pressure, diabetic foot, or venous-leg ulcers without any adversative effects. [ 27 , 28 ] However, studies have suggested that the reduced or compromised wound healing capacity in uncontrolled diabetic patients may be due to a reduction in growth factors and prolonged inflammatory responses due to increased proinflammatory cytokines in T2DM patients. [ 22 , 29 , 30 ] Thus, a modification in the protocol (rpm and time) for obtaining PRF in diabetic patients may be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Kartika et al evaluated the effect of topical use of autologous platelet-rich fibrin (A-PRF) and HA in DFU wound healing. The study was an open label, randomized, controlled trial conducted from July 2019 to April 2020 [47]. A combination of A-PRF + HA was applied on the surface of wounds and covered with bandage during the treatment period of 7 days.…”
Section: Ha In the Management Of Hard-to-heal Woundsmentioning
confidence: 99%